Floristic diversity and carbon stock of agroforestry systems in two municipalities of Northeast of State of Pará, Brazil - dos Santos, Silvio Roberto Miranda; Kato, Osvaldo Ryohei; Tourinho, Manoel Malheiros (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2018)
The objective of this study was to analyze the floristic and carbon stock (CS) of two types of agroforestry systems (SAF): traditional, in Cametá, Pará (SAF-CM), and commercial in Tomé-Açu, Pará (SAF-TA). We used plots of 50 m x 50 m, where the diameter at breast height (DBH) and the height of all individuals (ni) with DBH ≥ 5 cm were measured. The biomass of SAF was determined by the indirect method. They were inventoried on average in SAF-CM, 2,458 ni ha-1, belonging to 12 families, 19 genera and 19 species, while in SAF-TA, 1,249 ni ha-1, belonging to nine families, 13 genera and 13 species. Euterpe oleracea (açaí) and Theobroma cacao (cacau) were the most important species in the SAF studied. CS was higher in trees than in açaí and cacau. The management adopted influenced the species richness and CS. The SAF-CM showed higher resilience and the SAF-TA greater anthropy. Other species were found in abundance and CS: Virola surinamensis, Hevea brasiliensis and Carapa guianensis, in SAF-CM, and Spondias lutea, Bertholletia excelsa and Swietenia macrophylla, in SAF-TA. The results obtained put SAF as an alternative of production for consumption, sale and CS, ratifying the socioeconomic and environmental viability of these agroecosystems in the Amazon.